Psychoeducational Intervention for Perinatal Depression: Study Protocol of a Randomized Controlled Trial - Steardo, Luca; Caivano, Vito; Sampogna, Gaia; Di Cerbo, Arcangelo; Fico, Giovanna; Zinno, Francesca; Del Vecchio, Valeria; Giallonardo, Vincenzo; Torella, Marco; Luciano, Mario; Fiorillo, Andrea (Frontiers in Psychiatry, 2019)
Perinatal depression (PD) is a severe and disabling condition impacting negatively on children in terms of adverse neonatal outcomes and on the wellbeing of women and their families. All pregnant women attending the unit of Gynecology and Obstetrics Service of the University of Campania “L. Vanvitelli” will be screened for PD using the Edinburgh Postpartum Depression Scale (EPDS). Women with a score ≥ 10 at the EPDS will be invited to receive a full psychiatric assessment. The required sample size is of 126 women with PD which will be randomly allocated to either an experimental group, receiving a uni-familiar psychoeducational intervention, or to a control group, receiving the Best Treatment Option (BTO). Patients will be evaluated through several assessment instruments: Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Scale (HAM-A), Global Assessment of Functioning (GAF), Clinical Global Impression (CGI), Manchester Short Assessment of Quality of Life (MANSA), Family Assessment Device (FAD), Family Coping Questionnaire (FCQ) and Pattern of Care Schedule (PCS). Patients will be evaluated at baseline, 3, 6, 9 and 12 months post-randomization. The severity of depressive symptoms at the HAM-D scale has been selected as primary outcome. Other outcome measures include improvement in the severity of anxiety symptoms, of global and personal functioning, an improvement in family members’ coping strategies and in the level of quality of life. It has been highlighted the importance of developing screening and treating programs for PD, and our study will use rigorous study design to evaluate the efficacy of the adaption of a well-known family psychoeducational model to the treatment of PD. The aims of present trial are to: 1) develop an informative package for pregnant women with PD; 2) promote a screening programme for PD; 3) identify those (socio-demographic, pregnancy-related environmental) factors associated with a higher risk to develop a perinatal or postnatal depression; 4) evaluate the efficacy of a new experimental psychoeducational intervention in reducing the depressive symptoms during pregnancy compared to the BTO.